2022
DOI: 10.3390/agronomy12051101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Green Manure Combined with Phosphate Fertilizer on Movement of Soil Organic Carbon Fractions in Tropical Sown Pasture

Abstract: The application of green manure is a common way to increase the soil’s level of total organic carbon (TOC) and its fractions. However, the amount of green manure to apply and how the combined application of phosphate fertilizer affects the movement of TOC, and of its fractions, is still unclear. We conducted a column experiment with two treatments of phosphate fertilizer (with and without) and green manure (0, low amount level, high amount level). The longitudinal movement distance and accumulation amount of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Long-term growth of green manure crops improves SOM in Mediterranean region (Castellano-Hinojosa and Strauss, 2020; Repullo-Ruiberriz de Torres et al, 2021). Hu et al (2022) and Haruna (2019) also reported similar results in the tropics and subtropics. The above studies showed that long-term cultivation of green manure can significantly improve SOM, but this study did not significantly improve the SOM.…”
Section: Effect Of Intercropping On Soil Nutrient Contentssupporting
confidence: 68%
“…Long-term growth of green manure crops improves SOM in Mediterranean region (Castellano-Hinojosa and Strauss, 2020; Repullo-Ruiberriz de Torres et al, 2021). Hu et al (2022) and Haruna (2019) also reported similar results in the tropics and subtropics. The above studies showed that long-term cultivation of green manure can significantly improve SOM, but this study did not significantly improve the SOM.…”
Section: Effect Of Intercropping On Soil Nutrient Contentssupporting
confidence: 68%
“…It is possible to increase the grazing years to significantly change the taxonomic and functional diversities. In addition, we found that both taxonomic diversity and functional diversity have a significant impact on the function of P, and some studies have shown that soil P content in tropical regions is very low and thus is P-limited (Hu et al, 2022). Therefore, a slight change in the aboveground vegetation will change P functioning.…”
Section: Effects Of Vegetation Diversity On Soil Functionmentioning
confidence: 78%
“…However, phosphorus application reduced the proportion of POC, in the 40-60 cm soil layer, mainly because the effect of phosphorus fertilization on soil carbon was primarily occurs within the 0-30 cm soil layer, while nitrogen fertilization could affect SOC content in the 0-120 cm soil layer (Zhong et al, 2015). Similarly, it proved that phosphorus fertilization can increase POC content but does not affect its spatial distribution (Hu et al, 2022). The proportion of POC to SOC exhibited the highest values, suggesting that POC made the greatest contribution to SOC.…”
Section: Effect Of Nitrogen and Phosphorus Application On Soil Active...mentioning
confidence: 94%
“…It has been demonstrated that the application of phosphorus has an impact on the content of SOC, but not alter the geographical distribution of SOC fractions. (Hu et al, 2022). In contrast to the application of individual nutrients, the addition of nitrogen and phosphorus not only enhanced soil acidity but also mitigated the nitrogen and phosphorus deficiencies induced by single nutrient inputs.…”
Section: Introductionmentioning
confidence: 99%